APPROACHES TO THE DECENTRALIZATION IN A SELF-MANAGED PROVINCE: THE CONTEXT OF OVERLAPPING THE NEW CITY AND THE OLD CITY OF PHRA NAKHON SI AYUTTHAYA PROVINCE - Srithammakul, Surasak; Anusonphat, Nalaumon (Journal of Social Science and Cultural, 2023)
This article aims to present a self-managed provincial decentralized approach in the context of overlapping the new city with the old city of Phra Nakhon Si Ayutthaya Province. 6 approaches were presented, namely: 1) administrative structure Towns and livable communities should be developed to become cities of happiness. Upgrading the high-quality smart tourism industry Build a high-value economic base that is environmentally friendly with innovative technology and creative wisdom. Plans, projects and supervision should be made. develop and promote tourism Prevent and solve the problem of corruption and misconduct in the public sector. 3) People's participation Public participation should be created in the preparation of local development plans. Set village development goals (visions) for people to participate in planning policies and plans. Projects or activities in natural resources and environment, education, development, quality of life and society Infrastructure career promotion public utilities, religion and community welfare effectively and for the utmost benefit to communities in all areas. Aims to develop for Thai locals to work strong The government should reduce the level from controlling to overseeing local government organizations as necessary. 5) In terms of personnel, provinces should prepare personnel within the organization before establishing an autonomous province. In order to increase the efficiency of operations to truly achieve the objectives. 6) Organizational aspects The provinces should plan to decentralize power to local government organizations. prepare and show the ability to manage themselves provide resources local wisdom or local wisdom within the province sufficiently to manage and solve problems within the province.